Effect of Morphological and Environmental Parameters on Oleoresin Yield in Chir Pine (Pinus roxburghii Sargent) - Sharma, Kulwant Rai; Murtem, Ganguva; Lekha, Chander (Indian Forester, 2013)
Chir pine is commercially tapped for oleoresin. The oleoresin yield is affected by number of factors. The experiment was conducted to investigate the relationship of morphological parameters and climatic factors with oleoresin yield. The diameter at breast height, height, needle diameter, needle length and bark thickness showeda significant relationship with oleoresin yield. The number of primary branches, crown length has not shown significant relationship with oleoresin yield. The oleoresin yield was highly correlated with the temperature followed by evapotranspiration and sunshine hours. The factors like rainfall, humidity showed non-significant correlation with oleoresin yield; however, they have influenced temperature and evapotranspiration.